The Odyssey of D.H. Lawrence: Modernism, Europe and the New World - Marks, Peter (Miscelánea: A Journal of English and American Studies, 1999)
Literary modernism often exhibits the opposing impulses of cross-cultural pollination on the one hand, and exile and dislocation on the other. Writers wrestled with the problem of representing these complex cultural and political forces, especially as manifested in such European metropolises as Paris, Vienna, and London. D. H. Lawrence, in some ways an archetypal modem writer, differed from many modernist contemporaries in rejecting their Eurocentric viewpoint. Both his life and his writing display a search for fresh meanings, forms, and lifestyles in the so-called New World. This essay concentrates on two neglected, often heavily criticised novels of the 1920s, Aaron's Rod and Kangaroo, examining how each maps the distinct journeys of protagonists through and beyond a Europe terminally blighted by war. Lawrence recasts Europe as spiritually and culturally empty, but fundamentally unaware of its critical state. Aaron's Rod tracks the picaresque adventures of its eponymous hero from an English mining town, through the dulled world of western Europe to his apparent spiritual rebirth in Florence. Kangaroo records the more planned flight of Richard and Harriet Somers from a Europe they both detest to the supposed sanctuary of Australia. In neither novel is the search resolved: Aaron is pointed beyond Europe by his mentor, Lilly, while the Somers reject what they see as the unreflective ease of Australian democracy, journeying on to the untamed places of America. Both works overtly criticise the dead hand of post-war Europe from the margins of that culture, and beyond. At the same time, each is a literary experiment, an attempt by Lawrence to perform radical surgery on the novel form. As such they are worthy of consideration in discussion both of the eseentially European focus of much modernist literature and the diversity of literary essentially newness which marked it.